Mechanism-Driven Metabolic Engineering for Bio-Based Production of Free R-Lipoic Acid in Saccharomyces cerevisiae Mitochondria - Chen, Binbin; Foo, Jee Loon; Ling, Hua; Chang, Matthew Wook (Frontiers in Bioengineering and Biotechnology, 2020)
Lipoic acid is a valuable organosulfur compound used as an antioxidant for dietary supplementation, and potentially anti-diabetic and anti-cancer. Currently, lipoic acid is obtained mainly through chemical synthesis, which requires toxic reagents and organic solvents, thus causing environmental issues. Moreover, chemically synthesized lipoic acid is conventionally a racemic mixture. To obtain enantiomerically pure R-lipoic acid, which has superior bioactivity than the S form, chiral resolution and asymmetric synthesis methods require additional reagents and solvents, and often lead to wastage of S-lipoic acid or precursors with undesired chirality. Towards sustainable production of R-lipoic acid, we aim to develop a synthetic biology-based method using engineered yeast. Here, we deepened mechanistic understanding of lipoic acid biosynthesis and protein lipoylation in the model yeast Saccharomyces cerevisiae to facilitate metabolic engineering of the microbe for producing free R-lipoic acid. In brief, we studied the biosynthesis and confirmed the availability of protein-bound lipoate in yeast cells through LC-MS/MS. We then characterized in vitro the activity of a lipoamidase from Enterococcus faecalis for releasing free R-lipoic acid from lipoate-modified yeast proteins. Overexpression of the lipoamidase in yeast mitochondria enabled de novo free R-lipoic acid production in vivo. By overexpressing pathway enzymes and regenerating the cofactor, the production titer was increased ~2.9-fold. This study represents the first report of free R-lipoic acid biosynthesis in S. cerevisiae. We envision that these results could provide insights into lipoic acid biosynthesis in eukaryotic cells and drive development of sustainable R-lipoic acid production.